1996
DOI: 10.1128/mcb.16.9.4923
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Replication Intermediates in the Amplified CHO Dihydrofolate Reductase Domain by Two Novel Gel Electrophoretic Techniques

Abstract: Using neutral/neutral and neutral/alkaline two-dimensional (2-D) gel techniques, we previously obtained evidence that initiation can occur at any of a large number of sites distributed throughout a broad initiation zone in the dihydrofolate reductase (DHFR) domain of Chinese hamster ovary (CHO) cells. However, other techniques have suggested a much more circumscribed mode of initiation in this locus. This dichotomy has raised the issue whether the patterns of replicating DNA on 2-D gels have been misinterprete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 41 publications
0
15
1
Order By: Relevance
“…In two previous studies, novel variations of the neutralneutral and neutral-alkaline 2-D gel methods were developed to determine whether these methods could fail to detect a major initiation site near ori-␤ (22,23). Instead, the results supported our previous proposal that nascent-strand start sites are chosen from many potential sites scattered throughout the 55-kb intergenic region, with a concentration of sites in the central 30-to 35-kb encompassing the ori-␤ and ori-␥ regions (10,11,13,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In two previous studies, novel variations of the neutralneutral and neutral-alkaline 2-D gel methods were developed to determine whether these methods could fail to detect a major initiation site near ori-␤ (22,23). Instead, the results supported our previous proposal that nascent-strand start sites are chosen from many potential sites scattered throughout the 55-kb intergenic region, with a concentration of sites in the central 30-to 35-kb encompassing the ori-␤ and ori-␥ regions (10,11,13,39).…”
Section: Discussionmentioning
confidence: 99%
“…1, N/A 2-D) (11,13,39). Two recent variations of the 2-D gel methods that were designed specifically to detect a highly favored start site at ori-␤ failed to do so (22,23), lending support to a model in which potential initiation sites are scattered throughout the intergenic region, with ori-␤ and ori-␥ being only somewhat preferred.…”
mentioning
confidence: 83%
“…Furthermore, our previous suggestion that the Y-like species resulted from bubbles broken during processing (14) is undermined by other observations. First, Hamlin and co-workers have shown that broken replication bubbles form arcs distinct from a simple Y arc (23). Second, intact bubble arcs were seen with other enzymes such as HincII and ClaI (e.g.…”
Section: Initiation Arc Intensity Increases With Increasing Distancementioning
confidence: 99%
“…Our original interpretation depended on the assumption that molecules derived from O H -containing fragments coincident with a simple Y arc represented broken bubbles (14). The assumption was tenuous, given that it had been shown earlier that broken bubbles form arcs distinct from a simple Y arc (23).…”
mentioning
confidence: 99%
“…However, different techniques yield somewhat contradictory data regarding the exact sites of initiation, and origin activity appears to involve initiations throughout the region, with some degree of preference for initiation at three sites, called ori-␤, ori-␤Ј, and ori-␥ (Burhans et al 1990;Vaughn et al 1990;Kalejta et al 1996;Kobayashi et al 1998;Wang et al 1998). Attempts to identify DHFR replicators have so far yielded conflicting results.…”
mentioning
confidence: 99%